Adaptation and validation of the telepharmacy service adoption behavior questionnaire during the COVID-19 pandemic crisis - Indriyati Hadi Sulistyaningrum; Prasojo Pribadi; Seftika Sari (Intelektual Pustaka Media Utama, 2023)
Telepharmacy is an online application used to provide pharmaceutical services in the modern era. Therefore, this study aims to develop a questionnaire on a research model that integrates three well-known theories, namely the unified theory of acceptance and use of technology (UTAUT), the protection motivation theory (PMT), and the DeLone and McLean information success model, to determine factors that influence people’s behavior towards the adoption of telepharmacy services. A cross-sectional observational method was used with the purposive sampling technique. A total of 118 participants who were at least 18 years old received the questionnaire. They were selected using convenience sampling from a variety of population groupings. Data analysis was then performed with the exploratory factor analysis (EFA). Factor extraction was carried out using principal component analysis and varimax rotation. The results show 8 factors consisting of social influence and support 15.54%; understanding of proficiency, confidence and quality of information 11.06%; condition of facilities and skills 6.64%; severity and suffering 7.87%; time opportunity support and system quality 7.74%; intention to adopt telepharmacy 7.34%; perceived vulnerability 6.80%; and attitude 6.37%. Furthermore, the overall construct formed can explain 72.40% of the total variance. These results indicate that the telepharmacy service adoption behavior questionnaire is valid and reliable.